Research on the Root Cause of Cross-Listing - Fan, Yun-Xin (2020)
The existing hypotheses of cross-listing motivations could only explain part of cross-listing behaviours in a specific period or a specific economy. This paper attempts to find the deep logic of cross-listing motivations, which could explain all cross-listing behaviours.